Is patient education helpful in providing care for patients with rheumatoid arthritis? A qualitative study involving French nurses. (11th March 2013) - Fall, Estelle; Chakroun, Nadia; Dalle, Nathalie; Izaute, Marie
Abstract: This French study explored nurses' involvement in patient education for patients with rheumatoid arthritis. The study design was qualitative. Semistructured interviews were conducted with 16 hospital nurses. Data analysis was performed according to Giorgi's descriptive phenomenological method, and supported by specific qualitative analysis software (Sphinx). The results showed the important role of hospital nurses in rheumatoid arthritis care. Patient education is a core part of nurses' work, allowing them to give patients information and emotional support. The interviewees displayed skills in helping patients learn to care for themselves. However, patient education mostly concerned patients who are already committed to their health care. Non‐adherent patients warrant special attention; their acceptance of their disease, perceptions about disease and treatment, motivation, and autonomy should be specifically addressed. French nurses could benefit from more training, and could be aided by psychologists. Ambulatory services could also be developed for patient education in France, based on examples from other countries.